The Effects of School-based Physical Exercise With Different Cognitive Loads on Executive Functions - Shohre Mardasangi Dulabi; Mohammadreza Ghasemian; Mohammadali Aslankhani (Sport Sciences and Health Research)
Introduction: The present study aimed to compare the effects of 3 school-based physical exercises with different levels of cognitive engagement on executive functions. Materials and Methods: In total, 47 students aged 13-14 years were randomly divided into 3 groups, as follows: the Integrated Physical and Cognitive (IPC) exercise, peer physical exercise group (with the same physical challenge), and control group (the routine physical education program). A Continuous Performance Test (CPT), the N-back test, and the Stroop test were used to evaluate executive functions in pretest and posttest. Results: The obtained results indicated that the IPC group significantly improved more than the other groups on the executive functions. Accordingly, physical exercise with a higher cognitive load benefitted both speed and accuracy on cognitive tasks significantly more than the same physical activity alone. Conclusion: Therefore, in the integrated physical and cognitive exercise, the cognitive and physiological effects of this training style interact with each other; therefore, their beneficial effects can be gradually increased, while interventions that only focus on the physical dimension would be less effective in promoting cognitive functions.